(untitled) (Bangladesh Rice Journal, 2021)
Disease is one of the most limiting biotic factors that affects rice production worldwide. In Bangladesh, there are 10 rice diseases considered as major, which cause economic loss in farmers’ fields. Therefore, the aim of this article is to explore all the feasible avenues of technology deployment on rice disease management to restrict the disease infection at minimum level and thus minimize economic loss. The article is generated using data and/or infromation from published and unpublished works and incorporating authors’ experience. It is evident that periodically (odd year) a disease outbreak or epidemic occurred in Bangladesh such as blast. Under epidemic situation, research findings estimated a yield loss of up to 98% at the highest disease severity level of infection of blast. On the other hand, field survey indicated the highest of 65.4% yield loss from severly infected field with the disease. To overcome the epidemics in odd years and to keep the loss under economic threshold level, it is necessary to undertake preventive measures such as planting of resistant or tolerant varieties, use of disease-free seeds from healthy plants, use of balanced fertilizer where applicable, and following feasible crop rotations. Currently, it is urgent need for developing strong and precise weather-based disease-risk forecasting system at least one week’s lead time based on real-time weather data. Subsequent quick management options such as disease-specific fungicidal treatment should be communicated to all stakeholders using fast-delivery media such as TV channels and SMS could be efficient and effective ways to address the disease outbreak under epidemic situation. To address annualized yield loss, it is suggested to execute interventions like effective training to the root level (both for farmers and extension personnel) and conducting demonstration in farmers fields, regular field monitoring, digitalization in disease management sector, revive indigenous technologies as appropriate, and improving rice production system. To continously improve rice disease management sector, this paper has proposed an innovative action for three decades through to 2050 under the banner ‘Location, Variety and Disease Specific Smart Management’ on research, development and extension. Bangladesh Rice J. 25 (1) : 23-36, 2021